Mapping International Laws on Human Rights in the 1945 Constitution of the Republic Indonesia - Natamiharja, Rudi; Rasya, Al Gizca; Sabatira, Febryani (LPPM Universitas Lampung, 2021)
Human rights are granted by all people regardless of discriminatory differences. In this sense, human rights must be respected, guarded, and protected by individuals, broad society, and the State. Generally, human rights are outlined in several international instruments such as Universal Declaration on Human Rights (UDHR), International Covenant on Civil and Political Rights (ICCPR), and International Covenant on Economic, Social, and Cultural Rights (ICESCR) 1976. From a national perspective, Indonesia has played its roles in addressing and combating human rights violations by adopting some international provisions into the 1945 Constitution of the Republic Indonesia (Article 28) and ratifying several international instruments on human rights. Recognizing the correlation between international and national law, the study intends to examine to what extent Indonesia has adopted human rights material in international provisions into its constitution. The result of this study shows that almost all contents on human rights in article 28 of the 1945 Constitution of the Republic Indonesia are also contained in the Universal Declaration on Human Rights 1948. Several provisions on the International Covenant on Civil and Political Rights (ICCPR) and International Covenant on Economic, Social, and Cultural Rights (ICESCR) 1976 seem very similar to provided contents on the UDHR 1948. Therefore, it is undebatable that ICCPR and ICESCR also influence the inclusion of human rights contents in the 1945 Constitution on the second amendment in 2000.